Sensing and Stimulating Electrodes for Electroceuticals - Liu, Xiao; Wang, Kezhong; González-González, María Alejandra; Romero-Ortega, Mario; Wallace, Gordon G. (Frontiers in Sensors, 2022)
Electroceuticals is an emerging field that combines the technology in conductive materials with their capability to interface biological systems. The development of highly conductive electrodes to monitor human health in real-time while and simultaneously deliver stimulation are promising to revolutionize medical science. Aspects to consider during development include the desired shape, electrode material properties, number of active sites, carriers used, and methods of deployment and activation. Novel organic-conductor based electrode compositions offer properties unattainable with conventional metal electrodes. Emerging innovative deployment strategies communicate directly with target tissues while minimizing damage to the surrounding biological environment. Here we highlight he recent reported technology in platinized graphene fibers (sutrode), a high -performance electrode, capable of record electrophysiological signal from small autonomic nerves, which could bring us closer to the ultimate goal: modulating the activity of individual organs with high selectivity and precision for a therapeutic medical outcome. An in-depth understanding of electrode materials and methods of fabrication and deployment can provide unprecedented opportunities for electroceutical research.